Microbiota of Economically Important Fish in Colombia and Hungary: Probiotic Strategies for Growth and Health Improvement - Martin-Culma, Nazly Yolieth; Gil-Martinez, María Alejandra; Torres-Trujillo, Camilo; Coronado, Sandra M; Arenas, Nelson E; Bársony , Péter (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Fish-associated microbiota plays crucial roles in maintaining health and enhancing productivity. However, compared with those of mammals, the composition and functions of the fish microbiota remain less understood. Methods: A comprehensive analysis of the scientific literature was conducted to provide insights into diverse probiotic interactions and economically important fish species between Colombia and Hungary. Results: Improving growth performance, reflected by increased specific growth rates, increased weight gain, and increased feed conversion ratios, is closely linked to microbiota modulation. These growth benefits are accompanied by elevated immune responses, including increased lysozyme activity, upregulated complement and cytokine expression (e.g., IL-1β and TNF-α), and increased antioxidant enzyme activity (e.g., superoxide dismutase [SOD] and catalase [CAT]). Several trials also reported improvements in digestive enzyme activity (amylase, protease, and lipase) and intestinal morphology. Additionally, shifts in the gut microbiota composition characterized by a greater abundance of beneficial bacteria (e.g., lactic acid bacteria) and a reduction in pathogenic populations correlate with the upregulation of metabolic pathways involved in carbohydrate utilization and antioxidant defenses. Conclusions: These findings underscore the importance of understanding the ability of the fish microbiota to distinguish beneficial from pathogenic phenotypes, ultimately paving the way for innovative dietary strategies in aquaculture.